2019
DOI: 10.3390/app9214523
|View full text |Cite
|
Sign up to set email alerts
|

What is still Limiting the Deployment of Cellulosic Ethanol? Analysis of the Current Status of the Sector

Abstract: Ethanol production from cellulosic material is considered one of the most promising options for future biofuel production contributing to both the energy diversification and decarbonization of the transport sector, especially where electricity is not a viable option (e.g., aviation). Compared to conventional (or first generation) ethanol production from food and feed crops (mainly sugar and starch based crops), cellulosic (or second generation) ethanol provides better performance in terms of greenhouse gas (GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 7 publications
1
61
0
Order By: Relevance
“…As a result of persistent research and development in the last few years, the construction of plants using lignocellulose as feedstock has already begun [9]. However, their technological efficiency and reliability need to be proven [10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of persistent research and development in the last few years, the construction of plants using lignocellulose as feedstock has already begun [9]. However, their technological efficiency and reliability need to be proven [10].…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of the fuel production cost of a crop-based biofuel is the cost of the biomass feedstock, while the production of advanced biofuels requires installations with higher investment costs [6,14]. Globally, advanced ethanol production has stagnated, mainly due to technical difficulties and high production costs [15], and advanced ethanol made up less than 2% of the ethanol used in Sweden in 2018 [5]. The considerable financial risk means that long-term stable political incentives will be required for this type of ethanol production to be commercialized [6].…”
Section: Advanced Ethanol Productionmentioning
confidence: 99%
“…Several previous studies have shown that lignocellulosic ethanol production systems require economic support to be competitive with existing crop-based ethanol production systems, and especially so compared to fossil liquid fuels [15,[52][53][54]. The estimated production cost in the large-scale commercial production of lignocellulosic ethanol has been reported to be up to 30% higher than the production cost using existing wheat-based ethanol production in Sweden [47,51].…”
Section: Economic Consequences Of Ghg Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Second-generation ethanol derives from lignocellulosic raw materials, while first-generation ethanol derives from starch rich crops like corn or from sucrose rich crops such as sugarcane 1 . Despite the industrial production of second-generation biofuels yet being incipient; substantial research is being conducted for both production and conversion of raw materials 2 . Among the energetic crops, perennial grasses stand as the leading alternative, as their use overcome the major drawbacks of both the fossil fuels and the first-generation biofuels.…”
Section: Introductionmentioning
confidence: 99%